Employee Engagement and its Influencing Factors Among the Women Lecturers of Self-Financing Arts and Science Colleges in Chennai Region - Radhakrishnan , N. (International Journal of Psychosocial Rehabilitation, 2020)
In the competitive world, the employee involvement is the major feature for the success of the organization. Further the concept of employee engagement is also considered as a vital indicator for the success of the organization. Hence there is a need of employee engagement is to be studied by any successful organization. In this study an attempt is made to obtain the significant results on employee engagement among the selected women lecturers from self-financing arts and science colleges, Chennai. 200 respondents were selected and collected data using structured questionnaire and analyzed. The results shows that career development and organizational support were significantly predict employee engagement.